Validasi Metode Penetapan Bahan Aktif Permethrin dalam Insektisida dengan High Performance Liquid Chromatography (HPLC) - Walansyah, Hasbi Bagja; Afriani, Kartini; Salim, Agus; Kholidanata, Fareka (Politeknik AKA Bogor, 2023)
Insecticides are substances or chemicals that are used to kill or eradicate insects. One of the active ingredients contained in insecticide products is permethrin. One of the tests carried out was testing the levels of the active ingredient such as permethrin in insecticides. This testing was carried out by High Performance Liquid Chromatography (HPLC). This method is a new method that will be used for routine analysis testing laboratory at Laboratory. The method that is used refers to the journal Validated High Performance Liquid Chromatography (HPLC) Method for Quantifying Permethrin in Pharmaceutical Formulations. Therefore, it is necessary to validate this method regarding elements that can cause variations in the test results and identify factors that can affect the performance of the method and determine the magnitude of the effect. Based on the test results, it can be concluded that all the validation parameters of the testing method for determining the active ingredient permethrin by high performance liquid chromatography gave the results of specificity, linearity, instrument detection limit (LDI), quantitation limit (LQ), repeatability precision, intermediate precision, accuracy, and the rigidity of the method meets the CIPAC 3807 requirements. Keywords: Insecticide, Permethrin, CIPAC 3807 Keywords: Insecticide, Permethrin, CIPAC 3807